Endovascular Treatment of Acute Tibioperoneal Trunk Thrombosis. A Clinical Case Report - D. S. Chigidinova; B. A. Rudenko; A. S. Shanoyan; V. P. Mazaev; F. B. Shukurov (Креативная хирургия и онкология, 2019)
Introduction. Acute limb ischemia is a severe disorder caused by a sharp drop in the arterial perfusion of the limb. It carries a threat to the limb’s function and viability. The issue of early recognition of acute limb ischemia in surgery is both important and difficult. The current guidelines recommend that patients with acute limb ischemia when the limb is viable should be urgently examined and treated. Restoring the blood flow in patients with acute limb ischemia is a priority, since a significant reduction in arterial perfusion can lead to limb amputation and life-threatening complications. In acute limb ischemia different treatment methods can be used, both open surgery and endovascular procedures. The treatment strategy depends on the localisation, duration of ischemia, neurological deficit, concomitant diseases and risks associated with treatment and its results. Endovascular procedures on the arteries of the lower leg are most often indicated to save a limb. Endovascular procedures on the arteries of the lower leg are indicated more often in patients with critical limb ischemia. Endovascular procedures when the condition is primary demonstrate good outcomes and high efficiency on the arteries of the lower extremities at all levels of the lesion.Materials and methods. This paper presents a clinical case of a successful endovascular procedure performed for the treatment of acute thrombosis of the arteries of the lower leg. Three stents were implanted, with a good angiographically confirmed outcome.Conclusion. Endovascular balloon angioplasty with stenting of the tibioperoneal trunk can result in good outcomes in patients with acute thrombosis of the arteries of the lower leg.